Pro-Inflammatory Derangement of the Immuno-Interactome in Heart Failure - Kumar, Pavanish; Lim, Amanda; Poh, Su Li; Hazirah, Sharifah Nur; Chua, Camillus Jian Hui; Sutamam, Nursyuhadah Binte; Arkachaisri, Thaschawee; Yeo, Joo Guan; Kofidis, Theo; Sorokin, Vitaly; Lam, Carolyn S. P.; Richards, Arthur Mark; et al. (Frontiers in Immunology, 2022)
Chronic heart failure (HF) is a syndrome of heterogeneous etiology associated with multiple co-morbidities. Inflammation is increasingly recognized as a key contributor to the pathophysiology of HF. Heterogeneity and lack of data on the immune mechanism(s) contributing to HF may partially underlie the failure of clinical trials targeting inflammatory mediators. We studied the Immunome in HF cohort using mass cytometry and used data-driven systems immunology approach to discover and characterize modulated immune cell subsets from peripheral blood. We showed cytotoxic and inflammatory innate lymphoid and myeloid cells were expanded in HF patients compared to healthy controls. Network analysis showed highly modular and centralized immune cell architecture in healthy control immune cell network. In contrast, the HF immune cell network showed greater inter-cellular communication and less modular structure. Furthermore, we found, as an immune mechanism specific to HF with preserved ejection fraction (HFpEF), an increase in inflammatory MAIT and CD4 T cell subsets.